Effect of Training Transfer Factors on Employee Performance in the Airport Management Office of Mopah Class I Airport, Merauke - Saiful; Dewi Juliah Ratnaningsih; Suratini (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
This study aimed to examine the factors that affect transfer of training, namely social support, self-efficacy, and training transfer factors. This study also investigated the effect of training transfer on employee performance. This was a quantitative study with a causality analysis approach. The samples of this study consisted of all 104 employees at the Airport Management Office of Mopah Class I Airport, Merauke. The research instrument was a questionnaire with a 5-point Likert scale. The data collected were analyzed using the SEM-PLS method. The results of the data analysis showed that social support had a positive effect on transfer motivation and training transfer, but had no positive effect on employee performance. Self-efficacy had a positive effect on transfer motivation and employee performance, but no positive effect on training transfer. Transfer motivation had a positive effect on training transfer and was shown to mediate the relationship between social support and self-efficacy on training transfer. Training transfer had a positive effect on employee performance.